Cross-Country Skiing: Psychological, Motivational, and Attentional Aspects. (Sport and Exercise Psychology, 2025)
Cross-country skiing is a very popular winter Olympic sport, also widely practiced as a recreational activity. Although cross-country skiing is primarily considered one of the most physically demanding endurance sports, it is also highly demanding and complex from a technical, tactical, and psychological standpoint. It encompasses two main technical styles (classic and freestyle) and numerous subtechniques within these styles. The aspects of cross-country skiing, like endurance sports in general, most studied by sports psychologists are those related to psychological skills training, fatigue management, and attentive strategies.
Keywords: cross-country skiing; endurance sportsmotivation; psychological skills training; attentive strategies